2021
DOI: 10.5414/cncs110414
|View full text |Cite
|
Sign up to set email alerts
|

Forget the phosphorus: A case of hypervitaminosis D-induced symptomatic hypercalcemia

Abstract: Hypercalcemia is a frequently encountered electrolyte abnormality with a well-described differential diagnosis and classic algorithm for evaluation. The treatment for hypercalcemia is dependent on the underlying etiology. Hypervitaminosis D is an uncommon cause of hypercalcemia, but the use of vitamin D supplementation has expanded and case reports of supplemental vitamin D induced hypercalcemia have become more frequent. We present a case of hypervitaminosis D-induced altered mental status where diagnosis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This observation was reported previously and may result from low plasma renin and aldosterone in Black subjects [ 118 ]. In our study, cholecalciferol supplementation do not increases the absorption of phosphorus, which did not lead to deleterious hyperphosphatemia [ 119 ].…”
Section: Discussionmentioning
confidence: 91%
“…This observation was reported previously and may result from low plasma renin and aldosterone in Black subjects [ 118 ]. In our study, cholecalciferol supplementation do not increases the absorption of phosphorus, which did not lead to deleterious hyperphosphatemia [ 119 ].…”
Section: Discussionmentioning
confidence: 91%
“…The bioactive form of vitamin D, 1,25-dihydroxyvitamin D3 [1,25(OH) 2 D] or calcitriol, is biosynthesized by the kidneys from the storage form of vitamin D, 25(OH)D, and calcitriol increases dietary phosphate absorption in the intestines to increase serum Pi levels [85]. If serum Pi levels are high, the kidneys produce less calcitriol.…”
Section: Vitamin D and Hyperphosphatemiamentioning
confidence: 99%
“…Other authors have reported hypervitaminosis D with comparable features [2]. Hypophosphatemia is difficult to explain, as high calcitriol should increase intestinal and renal absorption [3]. Dysphagia and neuromuscular involvement are anecdotal in adults [4].…”
mentioning
confidence: 99%